Three-point sign in subacute combined degeneration of the spinal cord: A case report. Issue 31 (August 2018) - Zhang, Hai-Ning; Wang, Lei; Sun, Li; Yang, Yu
Abstract: Rationale: Subacute combined degeneration (SCD) of the spinal cord has been reported to have distinctive characteristics on magnetic resonance imaging (MRI), such as an "inverted V sign", a "pair of binoculars sign", and a "dot sign". We report a 3-point sign as a novel MRI characteristic, expanding the spectrum of imaging signs for SCD. Patient concerns: A 64-year-old female vegetarian presented with a 3-month history of progressive numbness and weakness in the lower extremities. Diagnosis: Laboratory examination showed a reduced serum vitamin B12 level. Spinal MRI showed hyperintensity within the posterior and lateral columns (appearing as a three-point sign) on T2-weighted imaging. Thus, the patient was diagnosed with SCD. Interventions: The patient was treated with intravenous cyanocobalamin and oral vitamin B12. Outcomes: After a follow-up period of 5 months, the symptoms were significantly improved. Lessons: Clinicians should be aware of this atypical MRI pattern, which may facilitate an early diagnosis.